Teeth, fossil record and evolutionary history of the cowtail stingray Pastinachus Rüppell, 1829. (21st October 2019) - Adnet, Sylvain; Mouana, Medhi; Charruault, Anne-Lise; Essid, El Mebrouk; Ammar, Hayet Khayati; Marzougui, Wissem; Merzeraud, Gilles; Tabuce, Rodolphe; Vianey-Liaud, Monique; Marivaux, Laurent
Abstract: Hypolophin 'dasyatids' are a common group of large stingrays today frequenting the Indo-Pacific inshores. Being often harvested in their restricted area, few are known about their biology and their evolutionary history despite a very peculiar dental pattern making it easy to track their fossil record. An abundant material consisting of isolated teeth from Late Bartonian (38–40 Ma) lagoonal deposits of Djebel el Kébar, Tunisia, allows to describe a new stingray, Pastinachus kebarensis nov. sp. This taxon represents the oldest occurrence for this genus but also the oldest fossil record for hypolophins. A dental comparison of these fossils with 3D rendered models of fresh specimens testifies that early hypolophin representatives had already a strongly arcuate and bulbous upper jaw, interlocking with a broad and elongated tooth plate on the lower jaw. This new fossil and its fossil relatives (here updated), indicate a pre-Bartonian origination for hypolophins in western Neotethys, and reveal a rapid and widespread colonization of the proto-Mediterranean Sea, western Atlantic and Indo-Pacific coasts during the late Paleogene–early Neogene. Finally, it is worth noting that early hypolophin representatives seemingly entered freshwater habitats occasionally as modern cowtail stingrays do.